IDENTIFICATION OF ANIMAL –VEHICLE COLLISION LOCATIONS ACCORDING TO EVALUATION OF DRIVER INJURIES AND VEHICLE DAMAGE IN THE KYIV REGION - Kokhan, Oleh (Proceedings of National Aviation University (archive), 2016)
Purpose: We have implemented the evaluation of identification of animal –vehicle collision (AVC) in Kyiv region in 2007-2014, using the methodology of descriptive statistics for three pairs of variables, which depend on the location of AVC: 1) "AVC location" and "number road" 2.) "AVC location" and "injury of the driver" 3.) "AVC location" and "damage of the vehicle." Methods: For the study we used the tests for the normal distribution of variables, that include: 1.) Table "Test of Normality", that used test Kolmogorov-Smirnova and Shapiro-Wilk, with taking into account the appropriate number of times for evaluation; 2. Histogram, which has a distribution for the relevant type of data according to normal distribution curve for visual comparison and further evaluation; 3) one of the functions of Descriptive Statistics, entitled Table "Descriptives", and which in turn uses two types of characteristics: a.) Skewness and b.) Kurtosis. Result: For the analysis we used IBM SPSS Statistics program, which allows to assess the correspondence of AVC to the normal distribution by including tests of Kolmogorov-Smirnov and Shapiro-Wilk. After passing the tests for each variable has been getting the word «Yes» or word «No» from SPSS. If the variable passed tests and its distribution corresponds to the normal distribution, the variable got the word «Yes». If the variable is not passed tests and its distribution is not responsible normal distribution, the variable got the word «No». Discussion: The appropriate assessment of location data was collected in the summary tables which allow to analyse the animal –vehicle collision locations on the roads in Kyiv region. It was found, that theoretical calculations to test normality in the SPSS program for many variables of all three factors «Road», «Damage», «Injuries» corresponds to the variable locations, but there are also a lot of variables that do not comply with the law of the normal distribution, although they have enough number of animal –vehicle collisions.